Peer Pressure and Smoking Behavior in Elementary School Students - Sinthura Vimalan Subramaniam; Arifah Nur Istiqomah; Eddy Fadlyana (Faculty of Medicine Universitas Padjadjaran, 2017)
Background:Adolescence is an important period in which many individuals are vulnerable to onset and progression of smoking. Peers are strongly associated with adolescent smoking initiation. This study is conducted to determine whether there is a relationship between peer pressure and smoking behavior in male elementary school students.Methods: A cross-sectional study was conducted in October 2014. Respondents were male students from grade four and five from state elementary schools (SDN) in Jatinangor district who voluntarily followed the research procedure. The sampling method used in this study was two-stage cluster sampling. A validated questionnaire was provided after getting informed consent from the respondents. The data analysis was performed using chi-square test.Results: As much as 110 male subjects were included in the study. Data showed that 57 students (51.8%) which were more than half of the number of students ever smoked and 53 students never smoked. Out of 110 students, 69 students (62.7 %) experienced peer pressure and 41 students (37.3%) never experienced peer pressure. The result of chi-square test from the study showed that the p-value is 0.000.Conclusions: There is a relationship between peer pressure and smoking behavior in male elementary school students in Jatinangor district. [AMJ.2017;4(1):1–5]DOI: 10.15850/amj.v4n1.1012